Antisipasi Degradasi Moral di Era Global - Muthohar, Sofa (Nadwa: Jurnal Pendidikan Islam, 2013)
In the globalization era, environment has a broad definition. Someone could very easily find an atmosphere that he likes. It brings to positive or negative effects. Teenagers (aged 12-22 years) are the generation most vulnerable to the negative influences that lead to moral decadence. This problem is verydifficult to overcome if it just rely on the secular West psychological theories. Islamic education is expected to provide a solution to these problems through functional strategy, integral and progressive. Religious teachings not only memorized but should also be presented in the spirit to assist youngpeople in solving the problem. This strategy could be: guiding problem solving in dealing with problems themselves and society as well as the formation of an integral understanding of his relationship with God. Teens should have spirit that can transform itself into a superior person.Â AbstrakDalam era globalisasi, lingkungan memiliki definisi yang luas. Seseorang bisa sangat mudah menemukan suasana yang dia suka sehingga memunculkan efek positif atau negatif. Remaja merupakan generasi yang paling rentan terhadap pengaruh negatif yang menyebabkan dekadensi moral. Masalah ini sangat sulit diatasi jika hanya mengandalkan teori-teori psikologi Barat yang sekuler. Pendidikan Islam diharapkan mampu memberikan solusi masalah ini melalui strategi yang fungsional, integral dan progresif. Ajaran agama tidak hanya dihafal tetapi juga harus dihadirkan dalam jiwa untuk mendampingi kaum muda dalam menyelesaikan masalahnya. Strategi ini bisa berupa: pembimbingan problem solving dalam menghadapi persoalan diri dan masyarakatnya serta pembentukan pemahaman secara integral tentang hubungannya dengan Allah. Remaja harus memiliki mental yang dapat merubah dirinya menjadi pribadi yang unggul.